Sytuacja języka białoruskiego w Internecie - Siwirska, Anna Berenika (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is devoted to the functioning of the Belarusian language in Internet communication. The author presents the results of her own research, in which she is interested in what language the Internet users write public and private messages, read news from the world or look for information. The author presents the linguistic situation on the Belarusian Internet and the functioning of the Belarusian language in various spheres of communication: in the mass media, social media, commentaries under press articles, websites of state institutions and private enterprises. Consequently, the real position and role of the Belarusian language in virtual communication is presented in the paper.